Plasmon Excitation in Single-walled Carbon Nanotubes Probed using charged particles: comparison of calculated and experimental spectra - Segui Osorio, Silvina Inda Maria (2013)
We study ‘ the excitation of plasmons due to the incidence of a fast charged particle that passes through a single-wall carbon nanotube. We use a quantized hydrodynamic model, in which the σ and π electron systems are depicted as two interacting fluids moving on a cylindrical surface. Calculations of the average number of the excited plasmons and the corresponding energy loss probability for the swift electrons are compared with several experimental results for electron energy loss spectra recorded using transmission electron microscopes. We are able to identify the π and σ + π plasmon peaks and elucidate the origin of various spectral features observed in different experiments.